ANALISIS KINERJA KEUANGAN PT. BANK PEMBANGUNAN DAERAH SULAWESI TENGGARA PADA PANDEMI COVID - Iink Pratiwi; Nofal Supriaddin; Miswar Rohansyah (Sigma: Journal of Economic and Business, 2022)
This research aims to determine and analyze: 1) Financial performance of PT. Southeast Sulawesi Regional Development Bank before and during the Covid 19 pandemic; 2) Differences in the financial performance of PT. Southeast Sulawesi Regional Development Bank before and during the Covid 19 pandemic.The results showed that: 1) The financial performance of PT. The Southeast Sulawesi Regional Development Bank before the Covid 19 pandemic was classified as healthy and during the Covid 19 pandemic it was quite healthy when viewed from the Loan to deposit ratio (LDR) indicator. Very healthy when observed from the Capital Adequacy Ratio (CAR) indicator. Non Performing Loans (NPL) and Return on Assets (ROA). Very healthy when observed from the Capital Adequacy Ratio (CAR) indicator. Non Performing Loans (NPL) and Return on Assets (ROA); 2) There is no significant difference in financial performance before the pandemic and during the Covid 19 pandemic at PT. The Southeast Sulawesi Regional Development Bank reviewed the Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Non Performing Loans (NPL) and Return On Assets (ROA).